Grave-to-cradle photothermal upcycling of waste polyesters over spent LiCoO2 - Xiangxi Lou; Penglei Yan; Binglei Jiao; Qingye Li; Panpan Xu; Lei Wang; Liang Zhang; Muhan Cao; Guiling Wang; Zheng Chen; Qiao Zhang; Jinxing Chen (Nature Communications, 2024)
Abstract Lithium-ion batteries (LIBs) and plastics are pivotal components of modern society; nevertheless, their escalating production poses formidable challenges to resource sustainability and ecosystem integrity. Here, we showcase the transformation of spent lithium cobalt oxide (LCO) cathodes into photothermal catalysts capable of catalyzing the upcycling of diverse waste polyesters into high-value monomers. The distinctive Li deficiency in spent LCO induces a contraction in the Co−O6 unit cell, boosting the monomer yield exceeding that of pristine LCO by a factor of 10.24. A comprehensive life-cycle assessment underscores the economic viability of utilizing spent LCO as a photothermal catalyst, yielding returns of 129.6 $·kgLCO −1, surpassing traditional battery recycling returns (13–17 $·kgLCO −1). Solar-driven recycling 100,000 tons of PET can reduce 3.459 × 1011 kJ of electric energy and decrease 38,716 tons of greenhouse gas emissions. This work unveils a sustainable solution for the management of spent LIBs and plastics.